Evaluation of Building Defects and Maintenance Management Practices in Jordanian Public Buildings: Causes, Impacts, and Strategies for Sustainable Improvement - Othman Ahmad Alnsour; Ala’a A. Alrwashdeh; Zakaria Al-Omari (Journal of Engineering Research and Reports, 2026)
Background: Building defects and inadequate maintenance management can compromise the safety, functionality, serviceability, and long-term performance of public buildings. In Jordan, empirical evidence linking defect assessment with systematic maintenance prioritisation remains limited. Aim: This study evaluated major building-defect categories in Jordanian public buildings, examined their principal causes and impacts, assessed existing maintenance practices, and developed an integrated framework to support sustainable maintenance management. Method: A sequential mixed-method approach combined field inspections, a structured questionnaire completed by 111 construction and maintenance professionals, case studies, and stakeholder consultations. Data were analysed using descriptive statistics, Mean Importance Score (MIS), Relative Importance Index (RII), standard deviation, normalised weights, and ranking analysis. Results: Structural defects were ranked highest (MIS = 4.61; RII = 0.922), followed by water- and moisture-related defects (MIS = 4.55; RII = 0.910) and mechanical, electrical, and plumbing defects (MIS = 4.48; RII = 0.896). Poor workmanship was the highest-ranked cause (MIS = 4.81; RII = 0.962), followed by poor maintenance practices (MIS = 4.76; RII = 0.952) and poor material quality (MIS = 4.72; RII = 0.944). Limited budgets, weak supervision, and non-standardised procedures also contributed to deterioration. Conclusion: The findings support a shift from predominantly reactive maintenance towards preventive and condition-based approaches. The proposed Building Defect Assessment and Maintenance Management Framework integrates defect identification, condition assessment, prioritisation, strategy selection, implementation, documentation, and performance monitoring to support more systematic lifecycle asset management in Jordanian public buildings.